Synthesis and characterisation of nanocrystalline ZnO for electronic applications - Pillai, Suresh C. (Trinity College (Dublin, Ireland). School of Chemistry, 2002)
The main focus of this work was to develop novel industrially viable procedures, based on sol gel technology, for the preparation of nano-size doped ZnO materials for varistor applications. Initially three well-established synthetic routes for the preparation of nanocrystalline ZnO were selected. Further doping and sintering of these materials showed that none of these methods could be used to produce a varistor material The poor electrical characteristics are attributed to the presence of impurity ions such as lithium and sodium. Thus it was decided to develop new processing routes to make nano-size ZnO and doped ZnO varistor materials. A novel synthetic procedure based on a non-hydrolytic sol gel condensation reaction was conducted and subsequent calcination at 500°C was used to make ZnO nano materials. ZnO precursor gels were prepared by the reaction of ethanolic solutions of zinc acetate and oxalic acid. Further drying and calcination produced ZnO nanoparticles of size ca. 30 nm. In a similar experiment chemical modifiers (diethanolamine and ethylene glycol) were added to the ethanolic solution of zinc acetate before the addition of oxalic acid. The gel formed was dried, calcined and characterised by electron microscopy and X-ray powder diffraction. Scanning Electron Microscopy studies revealed that these materials were composed of nanowires of 2 to 4 μm in length. Further investigations by Transmission Electron Microscopy showed that these wires consisted of approximately spherical nanoparticles of average diameter 21 ± 3 nm. The morphology of the wires was found to be similar to that previously reported for gold, silver, palladium and CdSe nanoparticle arrays. The precursor morphologies and formation mechanism of these wires were studied in detail by various techniques. Conventional solid-state mixing and core shell type doped varistors were fabricated from these materials. Core shell type material showed considerably higher breakdown voltage values compared to that of the other materials. Even though the electrical properties were superior, nearly full density was not achieved even at 1050°C. Studies were directed to make a better material with good densification and better electrical properties. A new procedure based on a mixed precursor route was performed to make nanosize doped ZnO materials. The synthesised powder had a particle size of 15 ± 3 run and a surface area as high as 45 m2/g. Dry ball milling for up to 30 minutes made less agglomerated nano powders. The milled powder was pelletised and sintered at various temperatures ranging from 700°C to 1050°C. 100% densification with a breakdown voltage of 941 ± 30 V/mm and a reasonably good α of 33 ± 3 were obtained for these materials conventionally sintered at 1050°C. A novel step sintering procedure was also tried for sintering these materials at lower temperature. Electrical measurements were carried out at various temperatures and a higher breakdown voltage (906 ± 30 V/mm) with considerably higher non-linear characteristics (α= 36 ± 3) compared to the commercial sample was obtained for step-sintered samples prepared from nano-size varistors. Phase analysis of the sintered samples was studied by powder X-ray Diffraction (XRD) and Energy Dispersive X-ray (EDX) analysis. Industrial pilot plant operations were successfully carried out in Littelfuse Ltd., Dundalk.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin